PEMBINAAN GURU DENGAN SISTEM ANGKA KREDIT - Sugiyono Sugiyono (Jurnal Cakrawala Pendidikan, 2002)
This research was aimed to evaluate the effectiveness of teacher's functional rank advancement by using Credit Number System. The policy of using credit number system in teacher's functional rank advancement is based on a decree ofMen-Pan in 1989 connected with decree No. 84 in 1993. The research was performed by means ofqualitative method. The source of data consists of the teachers, Principals,  Evaluating Team, and documentation. Data~gathering was triangulation, and data analysis was done by means of inductive methods through the process of data reduction, data display, and verification. Credibility of the data was examined through extended observation, improving persistence, triangulation, peer-check, and member check. The result showed that, first, the system of teacher's rank advancement by using credit number was perceived both positively and negatively. For potential teachers, this system better than pervious automatic rank advancement, but those who were indolent and not quite smart will give negative response, because teacher's wO,rk load will be heavier. Second, this credit grade system has actually not yet effective,as it cannot improve the teacher's motivation, achievementand professionalism; almost all proposals of rank advancement up to level IVla will be granted (without any obstacle) so that it seems like the automatic rank advancement; there was no--" correlation between the rank and teacher's professionalism; and after 13 years of application there was no teacher who can achieve the rank ofIV/c or over. Third, the main obstacle faced by the teachers in collecting the credit number for rank IVIb and above was in term of profession improvement (making paper, writing journal, doing research, etc). Fourth, although this system of teacher's rank advancement was not yet effective, the better system has not been found dealing with the era of regional autonomy. The system of teacher's rank advancement by using credit number was still considered the best compared to other systems. In that case, the effectiveness of this system should be improved by developing the ·promotion system of functional rank as that ofthe university lectures, where the amount of functional allowance is suited to the rank level. Besides,  there should be enough fund to perform seminars, do researches and write scientific paper; the procedure ofproposing rank advancement be made sample; and the evaluating team should master their work field and professional.